Enhancing EFL Students’ Listening Comprehension through Preparation for the TOEFL Application: Evidence from a Pre-Test–Post-Test Design - Johan, Andrian Nuriza; Chasanah, Zulia (Faculty of Education and Teacher Training of UIN Palopo, 2026)
Digital learning has increasingly been integrated into English language education due to the widespread accessibility of mobile technology. Nevertheless, the use of internet-based digital media for teaching listening skills in EFL contexts remains limited. This study aimed to examine the effectiveness of the Preparation for the TOEFL Test application in improving students’ listening comprehension and to explore students’ perceptions of its use as a mobile-assisted learning tool. This research employed a pre-experimental one-group pretest–posttest design involving 22 EFL undergraduate students. Listening comprehension was measured using a TOEFL-format listening test administered before and after a four-week intervention period. Quantitative analysis revealed a significant improvement in students’ listening performance. The mean score increased from 60.23 in the pretest to 73.73 in the posttest. A paired-samples t-test confirmed that this improvement was statistically significant (t = −17.173, p < 0.001), indicating that the application effectively enhanced students’ listening comprehension. Students’ perceptions were collected through a structured questionnaire. The results showed that most students responded positively to the application. More than 70% of participants agreed or strongly agreed that the application was easy to use, accessible anytime and anywhere, and helpful in supporting independent learning. The application’s structured materials and listening-focused features also increased students’ motivation and engagement in listening practice. The Preparation for the TOEFL Test application proved to be an effective mobile-assisted learning tool for improving EFL students’ listening comprehension while fostering positive learner perceptions.